2012
DOI: 10.1093/cvr/cvs337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of O-GlcNAc on cardioprotection by remote ischaemic preconditioning in non-diabetic and diabetic patients

Abstract: rIPC and diabetes mellitus per se influence myocardial O-GlcNAc levels through circulating humoral factors. O-GlcNAc signalling participates in mediating rIPC-induced cardioprotection and maintaining a state of inherent chronic activation of cardioprotection in diabetic myocardium, restricting it from further protection by rIPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 50 publications
6
90
0
2
Order By: Relevance
“…In previous studies, local pre‐ and postconditioning ex vivo has improved contractile function of atrial trabeculae during reoxygenation after sustained hypoxia 41, 42, 43, 44. Contractile function of atrial trabeculae was also improved during reoxygenation when plasma dialysate, taken from human volunteers after RIPC, was added before sustained hypoxia 45. The improved contractile function of atrial trabeculae in response to humoral transfer of cardioprotection was related to a posttranslational modification of proteins by O‐linked beta‐N‐acetylglucosamine 45.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In previous studies, local pre‐ and postconditioning ex vivo has improved contractile function of atrial trabeculae during reoxygenation after sustained hypoxia 41, 42, 43, 44. Contractile function of atrial trabeculae was also improved during reoxygenation when plasma dialysate, taken from human volunteers after RIPC, was added before sustained hypoxia 45. The improved contractile function of atrial trabeculae in response to humoral transfer of cardioprotection was related to a posttranslational modification of proteins by O‐linked beta‐N‐acetylglucosamine 45.…”
Section: Discussionmentioning
confidence: 90%
“…Contractile function of atrial trabeculae was also improved during reoxygenation when plasma dialysate, taken from human volunteers after RIPC, was added before sustained hypoxia 45. The improved contractile function of atrial trabeculae in response to humoral transfer of cardioprotection was related to a posttranslational modification of proteins by O‐linked beta‐N‐acetylglucosamine 45. In rat cardiomyocytes, such increased concentration of O‐linked beta‐N‐acetylglucosamines inhibited mPTP opening and reduced ROS formation 46.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of OGT in mice results in a diabetic phenotype (8), and increased levels of O-GlcNAc modification have been observed in cells and tissue from type 2 diabetes patients relative to healthy controls (9,15). Previously, we had reported that overexpression of OGT in keratinocytes (i) increases GlcNAc modification of cellular proteins and (ii) markedly enhances cell-cell adhesion (12).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ischemic preconditioning has been shown to increase cardiac O-GlcNAc levels (34,42); however, whether this contributes to the cardioprotection following this intervention is not known. Remote ischemic preconditioning also appears to influence myocardial O-GlcNAc levels, albeit through as yet unknown circulating factors (43). A number of other cardioprotective interventions have also been associated with increased O-GlcNAc levels (44 -46), raising the intriguing possibility that activation of O-GlcNAcylation could represent a nodal point linking diverse cardioprotective strategies.…”
Section: O-glcnacylation and The Heartmentioning
confidence: 99%